Management of Arterial Vasospasm Following Aneurysmal Subarachnoid Hemorrhage - Dusick, Joshua R.; Gonzalez, Nestor R. (Seminars in Neurology, 2013)
Despite recent advances, cerebral vasospasm and delayed cerebral ischemia (DCI) still represent a major cause of morbidity and mortality following aneurysmal subarachnoid hemorrhage (aSAH). Although a significant portion of the morbidity and mortality associated with aSAH is related to the initial hemorrhagic ictus, cerebral vasospasm and DCI are still the leading cause of poor outcomes and death in the acute posthemorrhage period, causing long-term disability or death in more than one in five of all patients who have suffered aSAH and initially survived.Management of patients following aSAH includes four major considerations: (1) prediction of patients at highest risk for development of DCI, (2) prophylactic measures to reduce its occurrence, (3) monitoring to detect early signs of cerebral ischemia, and (4) treatments to correct vasospasm and cerebral ischemia once it occurs. The authors review the pertinent literature related to each, including both the current management guidelines supported by the literature as well as novel management strategies that are currently being investigated.
Keywords: vasospasm; subarachnoid hemorrhage; stroke; delayed cerebral ischemia